A) lg²x-lg x²=-1 б) log₅((3x-1)(x+₅ 3x-1/x+3=0 в)log₂(x-4)+log₂(2x-1)=2log₂3

Alekskarpov Alekskarpov    2   22.06.2019 03:10    1

Ответы
5class1i 5class1i  17.07.2020 12:50
Первое и второе готово
 и третье готово - все в приложении

A) lg²x-lg x²=-1 б) log₅((3x-1)(x+₅ 3x-1/x+3=0 в)log₂(x-4)+log₂(2x-1)=2log₂3
A) lg²x-lg x²=-1 б) log₅((3x-1)(x+₅ 3x-1/x+3=0 в)log₂(x-4)+log₂(2x-1)=2log₂3
ПОКАЗАТЬ ОТВЕТЫ
oksanavolkova3 oksanavolkova3  17.07.2020 12:50
1)lg²x-2lgx+1=0
(lgx-1)²=0
lgx-1=0
lgx=1
x=10
2)(3x-1)(x+3)>0
x=1/3 U x=-3
x∈(-∞;-3) U (1/3;∞)
log(5)(3x-1)(x+3)*(x+3)/(3x-1)=0
log(5)(x+3)²=0
(x+3)²=1
x+3=-1 или х+3=1
х=-4 или х=-2 - не удов усл
3)x-4>0⇒x>4
2x-1>0⇒x>1/2
x∈(4;∞)
log(2)(x-4)(2x-1)=log(2)9
2x²-x-8x+4-9=0
2x²-9x-5=0
D=81+40=121
x1=(9-11)/4=-1/2 не удов усл
x2=(9+11)/4=5
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра